Optimized Resonators for Piezoelectric Power Conversion - Braun, Weston D.; Stolt, Eric A.; Gu, Lei; Jeronimo Segovia-Fernandez, Jeronimo; Chakraborty, Sombuddha; Lu, Ruochen; Rivas-Davila, Juan M. (IEEE open journal of power electronics, 2021)
The performance of inductors at high frequencies and small sizes is one of the largest limiting factors in the continued miniaturization of dc-dc converters. Piezoelectric resonators can have a very high quality factor and provide an inductive impedance between their series and parallel resonant frequencies, making them a promising technology for further miniaturizing dc-dc converters. In this paper we analyze the impact of resonator parameters on the performance of the piezoelectric resonator based dc-dc converter, derive the optimal load impedance and efficiency limits, and analyze the impacts of varying conversion ratio and load impedance. This work is accompanied by a prototype dc-dc converter using a piezoelectric resonator fabricated from lithium niobate. The piezoelectric resonator has a quality factor of 4178 and a coupling coefficient, k_t^2 , of 29%. The converter is able to achieve high efficiency zero voltage switching and a continuously variable conversion ratio without the use of any discrete inductors. It achieves a maximum power output of 30.9 W at an efficiency of 95.2% with a power density of 6.76 \frac{\text {W}}{\text {cm}^3} .